Building Consensus for Sustainable Development: Evaluation Theory Insights - Bova, Demetrio Miloslavo (European Journal of Sustainable Development, 2022)
The sustainable development goals orient the development path for each country by defining goals, sub-goals, and indicators for programming and control. The goals achievement is conditioned to the consensus of the populations involved; indeed, politicians cannot or do not want implement projects without gathering the necessary consensus. To achieve the demanded transition, tools evaluating a set of projects achieving targets, well-being, and consensus simultaneously are required. This manuscript enquires the generation of such tools by extensively debating willingness to pay and related techniques by seeking a theory bridging the actual value and actual consensus of projects. The outcome is a theoretical base useful to orient evaluation research toward the design of tools helpful to achieve sustainable development goals.